(untitled) - Siegfried, Donna Rae (Indianapolis, IN, 2006)
The Biology for Dummies book to everyday people or prospective students in the subject matter. It provides a good review of biology down to the cells and the beginning of life continuing to the inner workings of the human body.
Keywords: Biology,Sinh vật học